2010
DOI: 10.1093/nar/gkq809
|View full text |Cite
|
Sign up to set email alerts
|

The linker domain of basal transcription factor TFIIB controls distinct recruitment and transcription stimulation functions

Abstract: RNA polymerases (RNAPs) require basal transcription factors to assist them during transcription initiation. One of these factors, TFIIB, combines promoter recognition, recruitment of RNAP, promoter melting, start site selection and various post-initiation functions. The ability of 381 site-directed mutants in the TFIIB ‘linker domain’ to stimulate abortive transcription was systematically quantitated using promoter-independent dinucleotide extension assays. The results revealed two distinct clusters (mjTFIIB E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…The TFB B-reader and B-helix motifs, which connect the TFB ZR and -core domains, make intricate interactions with the inside of the RNAP clamp proximal to the active site. Mutational analysis of these structural elements in Mja and Pyrococcus furiosus (Pfu) TFB revealed conserved elements residing in the TFB linker region that are important for PIC stabilisation and synthesis of the initial phosphodiester bonds [29][30][31]. Is there more to the archaeal promoter than TATA and BRE?…”
Section: A Recruitment Cascade Nucleates Transcription Initiationmentioning
confidence: 99%
“…The TFB B-reader and B-helix motifs, which connect the TFB ZR and -core domains, make intricate interactions with the inside of the RNAP clamp proximal to the active site. Mutational analysis of these structural elements in Mja and Pyrococcus furiosus (Pfu) TFB revealed conserved elements residing in the TFB linker region that are important for PIC stabilisation and synthesis of the initial phosphodiester bonds [29][30][31]. Is there more to the archaeal promoter than TATA and BRE?…”
Section: A Recruitment Cascade Nucleates Transcription Initiationmentioning
confidence: 99%
“…Several yeast TFIIB-RNAP II co-crystals exist showing glimpses of the interactions between the TFIIB linker and the RNAP II surface and suggesting that the TFIIB linker penetrates the active centre cleft (22)(23)(24). Biochemical analyses demonstrated that the linker domain of TFIIB actively contributes to the catalytic activity of RNAP which in its presence is substantially higher than in its absence (25)(26)(27). The resolution of these RNAP II-TFIIB co-crystals is, however, poor and insufficient to either reveal or fully explain all the activities that TFIIB has in a PIC.…”
Section: The Tfiib/rnap Interface: Advantages Of Biochemical Analysismentioning
confidence: 99%
“…by substituting every amino acid residue of a given sequence by all 19 other amino acids) we were able to investigate the influence that TFIIB has on the catalytic activity of RNAP (26,27). This approach was facilitated by switching to a model system that at several occasions has proven its high degree of accessibility.…”
Section: The Tfiib/rnap Interface: Advantages Of Biochemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…High-throughput strategies and the automation of manual protocols on robotic liquid-handling platforms have created opportunities to perform such complex molecular biological procedures with little human intervention and minimal error rates [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%